2021
DOI: 10.1523/jneurosci.3073-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Altered Heterosynaptic Plasticity Impairs Visual Discrimination Learning in Adenosine A1 Receptor Knock-Out Mice

Abstract: Theoretical and modeling studies demonstrate that heterosynaptic plasticity -changes at synapses inactive during induction -facilitates fine-grained discriminative learning in Hebbian-type systems, and helps to achieve a robust ability for repetitive learning. A dearth of tools for selective manipulation has hindered experimental analysis of the proposed role of heterosynaptic plasticity in behavior. Here we circumvent this obstacle by testing specific predictions about changes in heterosynaptic plasticity, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The odor TMT has been used in several studies and the circuits activated by this odor are well understood ( Kobayakawa et al, 2007 ; Saito et al, 2017 ; Sakano, 2020 ). We also excluded confounding changes in anxiety and curiosity in the neuron-specific A 1 R-deficient mice that confirmed previous results using global A 1 R-deficient mice ( Chasse et al, 2021 ), whereas other studies have reported increased anxiety in A 1 R-deficient mice ( Johansson et al, 2001 ; Giménez-Llort et al, 2002 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The odor TMT has been used in several studies and the circuits activated by this odor are well understood ( Kobayakawa et al, 2007 ; Saito et al, 2017 ; Sakano, 2020 ). We also excluded confounding changes in anxiety and curiosity in the neuron-specific A 1 R-deficient mice that confirmed previous results using global A 1 R-deficient mice ( Chasse et al, 2021 ), whereas other studies have reported increased anxiety in A 1 R-deficient mice ( Johansson et al, 2001 ; Giménez-Llort et al, 2002 ).…”
Section: Discussionsupporting
confidence: 83%
“…The odor TMT has been used in several studies and the circuits activated by this odor are well understood (Kobayakawa et al, 2007;Saito et al, 2017;Sakano, 2020). We also excluded confounding changes in anxiety and curiosity in the neuron-specific A 1 R-deficient mice that confirmed previous results using global A 1 R-deficient mice (Chasse et al, 2021), whereas other studies have reported increased anxiety in A 1 Rdeficient mice (Johansson et al, 2001;Giménez-Llort et al, 2002). On the cellular level, immunostainings showed a reduced number of glutamatergic synapses in the external plexiform layer, and recordings of spontaneous PSCs in granule cells revealed a lower input frequency in the A 1 R flx/flx ;SNAP25 Cre mice.…”
Section: Discussionsupporting
confidence: 52%
“…Computational studies predicted the role of heterosynaptic plasticity in learning on sequential tasks. Evidence in support of this prediction for organism-level learning was provided in a recent work demonstrating that impairment of heterosynaptic plasticity in adenosine A1 receptor knockout mice is accompanied by a selective impairment of re-learning on consequent tasks but no impairment in the initial learning (Chasse et al, 2021 ). Results of the present study propose an additional role, which non-associative heterosynaptic plasticity could play at GABA-ergic synapses during maturation of newborn granule cells in the adult dentate gyrus.…”
Section: Discussionmentioning
confidence: 84%
“…Three trains (one per minute) of 10 bursts (at 1 Hz) of depolarizing pulses were applied. Prior research showed that intracellular tetanization can induce bidirectional plasticity (LTP or LTD) in excitatory and inhibitory neurons in the visual cortex (Volgushev et al, 2000 , 2016 ; Bannon et al, 2017 ; Chistiakova et al, 2019 ; Chasse et al, 2021 ), in the auditory cortex (Lee et al, 2012 ), and in the hippocampus (Kuhnt et al, 1994 ). Similar protocols, consisting of postsynaptic spikes without presynaptic activation, can induce plasticity of inhibitory transmission in visual (Kurotani et al, 2003 , 2008 ) and somatosensory (Lourenço et al, 2014 ) cortex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation